Revisiting signs, strengths and weaknesses of Standard Chest Radiography in patients of Acute Dyspnea in the Emergency Department - Cardinale, Luciano; Volpicelli, Giovanni; Lamorte, Alessandro; Martino, Jessica; veltri, Andrea (Journal of Thoracic Disease; Vol 4, No 4 (August 21, 2012): Journal of Thoracic Disease, 2012)
Dyspnoea, defined as an uncomfortable awareness of breathing, together with thoracic pain are two of the most frequent symptoms of presentation of thoracic diseases in the Emergency Department (ED). Causes of dyspnoea are various and involve not only cardiovascular and respiratory systems. In the emergency setting, thoracic imaging by standard chest X-ray (CXR) plays a crucial role in the diagnostic process, because it is of fast execution and relatively not expensive. Although radiologists are responsible for the final reading of chest radiographs, very often the clinicians, and in particular the emergency physicians, are alone in the emergency room facing this task. In literature many studies have demonstrated how important and essential is an accurate direct interpretation by the clinician without the need of an immediate reading by the radiologist. Moreover, the sensitivity of CXR is much impaired when the study is performed at bedside by portable machines, particularly in the diagnosis of some important causes of acute dyspnoea, such as pulmonary embolism, pneumothorax, and pulmonary edema. In these cases, a high inter-observer variability of bedside CXR reading limits the diagnostic usefulness of the methodology and complicates the differential diagnosis. The aim of this review is to analyze the radiologic signs and the correct use of CXR in the most important conditions that cause cardiac and pulmonary dyspnoea, as acute exacerbation of chronic obstructive pulmonary disease, acute pulmonary oedema, acute pulmonary trombo-embolism, pneumothorax and pleural effusion, and to focus indications and limitations of this diagnostic tool.